Assessing the photochemical lifetimes of the sulfonamide antibiotic sulfamethoxazole, of significance for sunlit freshwaters - Sara Abdelli; Luca Carena; Enmanuel Cruz Muñoz; Davide Ballabio; Viviana Consonni; Roberto Todeschini; Javier Marugán; Ángela García-Gil; Paola Calza; Laura Ferrando-Climent; Davide Vione (Journal of Environmental Chemical Engineering, 2026)

Wildfire ash impacts the early development of the sea urchin Paracentrotus lividus - Roberta Miroglio; Pietro Soro; Sara Ferrando; Giacomo Rosa; Michele Oneto; Paolo Bianchini; Marco Faimali; Simone Farina; Chiara Gambardella (Marine Environmental Research, 2026)

Repeated aluminum ingestion alters human intestinal structure: focus on advanced 3D tissue models - Giulia De Negri Atanasio; Lorenzo Dondero; Francesca Tardanico; Giorgia Allaria; Erica Lertora; Giacomo Rosa; Chiara Barisione; Caterina Ivaldo; Francesca Rispo; Tommaso Filippini; Ilaria Demori; Sara Ferrando; et al. (Pflügers Archiv - European Journal of Physiology, 2026)

Defining early carcinogenic markers for the prediction of the hazard potential of mineral fibres in an in vitro human 3D bronchial model - Vanessa Almonti; Serena Mirata; Mario Passalacqua; Stefania Vernazza; Sara Tirendi; Sara Ferrando; Beatrice Risso; Elena Grasselli; Giulia De Negri Atanasio; Anna Maria Bassi; Alessandro F. Gualtieri; Sonia Scarfì (Archives of Toxicology, 2026)
This study aimed to identify early carcinogenic markers to predict the hazard potential of mineral fibres using a human 3D bronchial model. Traditional 2D cell models inadequately mimic lung complexity, prompting the use of more physiologically relevant 3D systems. We investigated the effects of crocidolite (CRO) and two size fractions of chrysotile (≤ and > 5 μm length: CHR S and CHR L) to elucidate early toxicological mechanisms and relate them to the IARC key characteristics (KCs) of carcinogens. Initial analyses (MTT, TEER, and histology) at 24–48 h showed a transient acute toxicity and tissue resilience, indicating limited predictive value at this time point. However, after 12 d of exposure, fibre-treated tissues exhibited persistent alterations corresponding to established IARC KCs, suggesting the early onset of cell transformation pathways. Key findings included: sustained inflammatory signalling, characterized by prolonged overexpression of IL-1β, IL-6, and IL-8; ii) persistent genotoxicity, marked by the prolonged nuclear positivity of γH2AX, indicating DNA double-strand breaks without significant cell death; and iii) induction of fibrotic and epithelial-to-mesenchymal transition (EMT) signals, including the increased expression of key markers such as TGF-β, VEGF, ZEB-2, N-Cadherin, Vimentin, and Mesothelin. These alterations correspond to IARC KCs 2, 6, and 8. They were observed within a short time frame of tissue treatment and could serve as reliable, early predictive endpoints for in vitro toxicological tests. We propose that integrating these specific KC-based biosignatures in 3D lung models with physicochemical fibre characterization may provide a robust framework for predictive assessment of inhalable fibre carcinogenicity.

Marine heatwaves have no impact on fertilization, early development and sensitivity to metal toxicity in the sea urchin Paracentrotus lividus - Chiara Gambardella; Pietro Soro; Roberta Miroglio; Sara Ferrando; Giacomo Rosa; Marco Faimali; Laura Tamburello (Marine Environmental Research, 2026)

Seed banking of mediterranean coastal plants: an analysis to identify current seed availability and gaps to guide future seed collection and habitat restoration activities - Marcello De Vitis; Valter Di Cecco; Mohamed Abdelaal; Gianluigi Bacchetta; Jože Bavcon; Kenza Saadiya Benmenni; Maurizio Bianchelli; Magda Bou Dagher Kharrat; Joseph A. Buhagiar; Francesca Carruggio; Angelino Carta; Simona Casavecchia; et al. (Journal of Coastal Conservation, 2025)

Towards a European sustainable beneficiation of rare earth elements bearing minerals: a review - Niroshan Gajendra; Duygu Yilmaz; Maria Cristina Vila; Maria de Lurdes Dinis; Erika Andrea Levei; Anamaria Iulia Török; Deniz Avsar; Anastasios Kladis; Athina Preveniou; Anne Merrild Hansen; Sara Bjørn Aaen; Laura Ferrando-Climent (Science of The Total Environment, 2025)

Lipid distribution and composition in Antarctic toothfish before and after reproductive migration: implications for the life cycle - Davide Di Blasi; Stefano Aicardi; Giorgia Allaria; Erica Carlig; Sara Ferrando; Laura Ghigliotti; Elena Grasselli; Annalisa Salis; Marino Vacchi; Steven J. Parker (Polar Biology, 2024)

Insight on thermal stress response of demosponge Chondrosia reniformis (Nardo, 1847) - Maha Moussa; Marina Pozzolini; Sara Ferrando; Asma Mannai; Eleonora Tassara; Marco Giovine; Khaled Said (Science of The Total Environment, 2024)

Innovations in geomatics teaching during the COVID-19 emergency - Matteo Botto; Bianca Federici; Ilaria Ferrando; Sara Gagliolo; Domenico Sguerso (Applied Geomatics, 2023)
The approach in the teaching process is changing, thanks to the increased awareness that a higher students’ involvement leads to a better quality of their learning. The aim is to make the students more participative, avoiding a unidirectional lesson and encouraging their wish to keep updated on the course advancements. However, innovative teaching methodologies are not yet widespread, mainly in STEM (Science, Technology, Engineering, and Mathematics) disciplines. At the University of Genoa, the experimentation of innovative teaching techniques has been significant and worthy especially because it was planned before the COVID-19 emergency and applied in the scenario of forced remote teaching. Thanks to the introduction of novel technological instruments, several techniques have been exploited to realize interactive lessons and promoting students’ involvement. The present work discloses the employed techniques and frames them within the state of the art of innovative teaching, highlighting their contribution in the teaching activities related to the Geomatics field of knowledge. The acquired experiences in Geomatics dissemination and a critical analysis, including teachers’ and students’ perception about the tested innovative teaching/learning tools, are also reported. In general, the innovations introduced in teaching and learning processes during the COVID-19 sanitary emergency were warmly received by the entire community, including teachers, students, and teaching assistants.

Multi-Platforms and Multi-Sensors Integrated Survey for the Submerged and Emerged Areas - Ali Alakbar Karaki; Marco Bibuli; Massimo Caccia; Ilaria Ferrando; Sara Gagliolo; Angelo Odetti; Domenico Sguerso (Journal of Marine Science and Engineering, 2022)
In this paper, the state-of-the-art concerning new methodologies for surveying in coastal areas in order to obtain an efficient quantification of submerged and emerged environments is described and evaluated. This work integrates an interdisciplinary approach involving both geomatics and robotics and focuses on definition, implementation, and development of a methodology to execute integrated aerial and underwater survey campaigns in shallow water areas. A preliminary test was performed at Gorzente Lakes near Genoa (Italy), to develop and integrate different survey techniques, enabling working in a smarter way, reducing costs and increasing safety for the operators. In this context, Remote Sensing techniques were integrated with a UAV (Unmanned Aerial Vehicle) carrying an aerial optical sensor for photogrammetry and with an ASV (Autonomous Surface Vehicle) expressly addressed to work in extremely shallow water with underwater acoustic sensors (single echo sounder). The obtained continuous seamless DSM (Digital Surface Model) for the entire environment was reconstructed by the combination of different sensing systems by limiting reliance on the GNSS (Global Navigation Satellite System) support. The obtained DSM was displayed in a 3D model leading to the evaluation of the water flow volume and rendering of 3D visualization.

Midtrophic fish feeding modes at the poles: an ecomorphological comparison of polar cod (Boreogadus saida) and Antarctic silverfish (Pleuragramma antarctica) - Erica Carlig; Jørgen S. Christiansen; Davide Di Blasi; Sara Ferrando; Eva Pisano; Marino Vacchi; Richard L. O’Driscoll; Laura Ghigliotti (Polar Biology, 2021)
The polar cod (Boreogadus saida ) and the Antarctic silverfish ( Pleuragramma antarctica ) are pelagic fish endemic to the Arctic and Antarctica sea, respectively. Both species are abundant and play a central role as midtrophic wasp-waist species in polar ecosystems. Due to their biological and ecological characteristics (small size, complex life histories, relatively short generation cycles, movement capability, planktivorous diet, and importance as prey), the polar cod and the Antarctic silverfish are potentially good sentinels of ecosystem change. Changes in polar zooplankton communities are well documented. How changes impact ecosystems as a whole largely depend on the degree of diet specialization and feeding flexibility of midtrophic species. Here, we provide the ecomorphological characterization of polar cod and Antarctic silverfish feeding performances. A comparative functional ecology approach, based on the analysis of morpho-anatomical traits, including calculation of suction index and mechanical advantage in jaw closing, was applied to profile the feeding modes and flexibility of the two species. Ecomorphological evidence supports differences in food acquisition: the polar cod appears able to alternate particulate ram-suction feeding to a pump filter feeding, and the Antarctic silverfish results be both a particulate ram and a tow-net filter feeder. Both species exhibit opportunistic feeding strategies and appear able to switch feeding mode according to the abundance and size of the available prey, which is a clue of potential resilience to a changing environment.

Olfaction in the Antarctic toothfish Dissostichus mawsoni: clues from the morphology and histology of the olfactory rosette and bulb - Sara Ferrando; Andrea Amaroli; Lorenzo Gallus; Davide Di Blasi; Erica Carlig; Marino Rottigni; Marino Vacchi; Steven J Parker; Laura Ghigliotti (Polar Biology, 2019)

Fipronil (Phenylpyrazole) induces hemato-biochemical, histological and genetic damage at low doses in common carp, Cyprinus carpio (Linnaeus, 1758) - Abdul Ghaffar; Riaz Hussain; Ghulam Abbas; Mujahid Kalim; Ahrar Khan; Sara Ferrando; Lorenzo Gallus; Zulfiqar Ahmed (Ecotoxicology, 2018)

Surface egg structure and early embryonic development of the Antarctic toothfish, Dissostichus mawsoni Norman 1937 - Laura Ghigliotti; Sara Ferrando; Davide Di Blasi; Erica Carlig; Lorenzo Gallus; Darren Stevens; Marino Vacchi; Steven J Parker (Polar Biology, 2018)

Reproductive features of the Antarctic silverfish (Pleuragramma antarctica) from the western Ross Sea - Laura Ghigliotti; Sara Ferrando; Erica Carlig; Davide Di Blasi; Lorenzo Gallus; Eva Pisano; Stuart Hanchet; Marino Vacchi (Polar Biology, 2017)

Evaluation of the Acquisition of the Aerobic Metabolic Capacity by Myelin, during its Development - Silvia Ravera; Martina Bartolucci; Patrizia Garbati; Sara Ferrando; Daniela Calzia; Paola Ramoino; Maurizio Balestrino; Alessandro Morelli; Isabella Panfoli (Molecular Neurobiology, 2016)

Support of Nerve Conduction by Respiring Myelin Sheath: Role of Connexons - Silvia Ravera; Martina Bartolucci; Enrico Adriano; Patrizia Garbati; Sara Ferrando; Paola Ramoino; Daniela Calzia; Alessandro Morelli; Maurizio Balestrino; Isabella Panfoli (Molecular Neurobiology, 2016)

Molecular Cloning, Characterization, and Expression Analysis of a Prolyl 4-Hydroxylase from the Marine Sponge Chondrosia reniformis - Marina Pozzolini; Sonia Scarfì; Francesca Mussino; Sara Ferrando; Lorenzo Gallus; Marco Giovine (Marine Biotechnology, 2015)

Skip spawning as a reproductive strategy in Antarctic fish species: the Antarctic silverfish (Pleuragramma antarctica) case study - Ghigliotti Laura; Ferrando Sara; Carlig Erica; Di Blasi Davide; Gallus Lorenzo; Pisano Eva; Hanchet Stuart; Vacchi Marino (Frontiers in Marine Science, 2015)

The peripheral olfactory organ in the Greenland shark Somniosus microcephalus (Bloch and Schneider, 1801) - Ferrando Sara; Gallus Lorenzo; Ghigliotti Laura; Vacchi Marino; Nielsen Julius; Christiansen Jorgen; Pisano Eva (Frontiers in Marine Science, 2015)

Effects of urea on the molecules involved in the olfactory signal transduction: a preliminary study on Danio rerio - Sara Ferrando; Lorenzo Gallus; Chiara Gambardella; Emiliano Marchesotti; Silvia Ravera; Valeria Franceschini; Maria Angela Masini (Fish Physiology and Biochemistry, 2014)

Effects of selected metal oxide nanoparticles on Artemia salina larvae: evaluation of mortality and behavioural and biochemical responses - Chiara Gambardella; Tina Mesarič; Tamara Milivojević; Kristina Sepčić; Lorenzo Gallus; Serena Carbone; Sara Ferrando; Marco Faimali (Environmental Monitoring and Assessment, 2014)

Presence and distribution of serotonin in the stomach of the Antarctic silverfish Pleuragramma antarcticum - Chiara Gambardella; Laura Ghigliotti; Lorenzo Gallus; Eva Pisano; Grazia Tagliafierro; Sara Ferrando (Polar Biology, 2012)

The tongue morphology and lingual gland histochemistry of Ligurian Sea odontocetes - Tiziana Ferrando; Federico Caresano; Sara Ferrando; Lorenzo Gallus; Maurizio Wurtz; Grazia Tagliafierro (Marine Mammal Science, 2010)

Born among the ice: first morphological observations on two developmental stages of the Antarctic silverfish Pleuragramma antarcticum, a key species of the Southern Ocean - Massimiliano Bottaro; Diana Oliveri; Laura Ghigliotti; Eva Pisano; Sara Ferrando; Marino Vacchi (Reviews in Fish Biology and Fisheries, 2009)

The GABAergic-like system in the cyprid of Balanus amphitrite (=Amphibalanus amphitrite) (Cirripedia, Crustacea) - Lorenzo Gallus; Sara Ferrando; Chiara Gambardella; Alberto Diaspro; Paolo Bianchini; Veronica Piazza; Giambattista Bonanno; Marco Milanese; Paola Ramoino; Grazia Tagliafierro (Biofouling, 2009)

Born among the ice: first morphological observations on two developmental stages of the Antarctic silverfish Pleuragramma antarcticum, a key species of the Southern Ocean - Massimiliano Bottaro; Diana Oliveri; Laura Ghigliotti; Eva Pisano; Sara Ferrando; Marino Vacchi (Reviews in Fish Biology and Fisheries, 2009)

Gamma-aminobutyric acid and related molecules in the sea fan Eunicella cavolini (Cnidaria: Octocorallia): a biochemical and immunohistochemical approach - Laura Girosi; Sara Ferrando; Francesco Beltrame; Gaetano Ciarcia; Alberto Diaspro; Marco Fato; Mirko Magnone; Luca Raiteri; Paola Ramoino; Grazia Tagliafierro (Cell and Tissue Research, 2007)